The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1152/physrev.00009.2005
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenic Mechanisms and Their Hormonal Regulation

Abstract: Increased heat generation from biological processes is inherent to homeothermy. Homeothermic species produce more heat from sustaining a more active metabolism as well as from reducing fuel efficiency. This article reviews the mechanisms used by homeothermic species to generate more heat and their regulation largely by thyroid hormone (TH) and the sympathetic nervous system (SNS). Thermogenic mechanisms antecede homeothermy, but in homeothermic species they are activated and regulated. Some of these mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
468
1
20

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(511 citation statements)
references
References 246 publications
15
468
1
20
Order By: Relevance
“…Thyroid hormone also plays a crucial role in adaptive thermogenesis. The full thermogenic response of BAT requires ligation of nuclear thyroid hormone receptors (transcription factors) which increases the sensitivity of BAT cells to adrenergic stimulation allowing UCP-1 expression [16,17].…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormone also plays a crucial role in adaptive thermogenesis. The full thermogenic response of BAT requires ligation of nuclear thyroid hormone receptors (transcription factors) which increases the sensitivity of BAT cells to adrenergic stimulation allowing UCP-1 expression [16,17].…”
Section: Glossarymentioning
confidence: 99%
“…Thyroid hormone also plays a crucial role in adaptive thermogenesis. The full thermogenic response of BAT requires ligation of nuclear thyroid hormone receptors (transcription factors) which increases the sensitivity of BAT cells to adrenergic stimulation allowing UCP-1 expression [16,17].While it is obvious that mice have a very large body surface area to volume ratio compared to humans, it is not generally realized that this results in rapid heat loss to their environment whenever ambient temperature falls below thermoneutrality. In addition, because of their small size, mice cannot bear enough fur or fat insulation to prevent heat loss to their environment.…”
mentioning
confidence: 99%
“…The classical theory of thyroid hormone regulation of metabolism is that T4 is activated in the peripheral tissues such as muscle or liver, thus stimulating energy expenditure through mitochondrial uncoupling or acceleration of the turnover of ATP-utilizing enzymes (55). A recent study suggests that there may be a direct effect of T3 to inhibit AMP kinase in the ventro-medial hypothalamus leading to upregulation of de novo lipogenesis in the hypothalamus.…”
Section: Deiodinases and Metabolic Controlmentioning
confidence: 99%
“…Conversely, hypothyroid patients often suffer from weight gain and bradycardia (3). While most of the cardiovascular and metabolic effects of thyroid hormone have been attributed to direct actions in the corresponding peripheral tissues, such as heart (4) or skeletal muscle and fat (5,6), recent studies have demonstrated that the hormone modulates these processes also through the brain (7): injections of thyroid hormone into different brain regions stimulate energy expenditure (8), and thyroid hormone signaling is required to establish the metabolic set point during embryonal development (9,10).…”
Section: Introductionmentioning
confidence: 99%